2015
DOI: 10.1086/683811
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mutant Bone Morphogenetic Protein Receptor II Worsens Pulmonary Hypertension Secondary to Pulmonary Fibrosis

Abstract: Pulmonary fibrosis is often complicated by pulmonary hypertension (PH), and previous studies have shown a potential link between bone morphogenetic protein receptor II (BMPR2) and PH secondary to pulmonary fibrosis. We exposed transgenic mice expressing mutant BMPR2 and control mice to repetitive intraperitoneal injections of bleomycin for 4 weeks. The duration of transgene activation was too short for mutant BMPR2 mice to develop spontaneous PH. Mutant BMPR2 mice had increased right ventricular systolic press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…For example, HIF1-α mediates TGF-β1-induced Snail and TWIST1 expression in breast cancer cells (26). Qian et al (27) reported that TGF-β1 affects the nuclear translocation activity of HIF1-α in NiONPs-induced pulmonary fibrosis. Similarly, mutant BMPR2 expression resulted in an increase of HIF1-α in mouse pulmonary vascular endothelial cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HIF1-α mediates TGF-β1-induced Snail and TWIST1 expression in breast cancer cells (26). Qian et al (27) reported that TGF-β1 affects the nuclear translocation activity of HIF1-α in NiONPs-induced pulmonary fibrosis. Similarly, mutant BMPR2 expression resulted in an increase of HIF1-α in mouse pulmonary vascular endothelial cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular permeability in the lungs was quantitated using an AngioSense 750EX Fluorescent Imaging Agent (PerkinElmer) with spectroscopic imaging in a LI-COR Pearl Impulse Small Animal Imager (97). Elevated pulmonary artery pressure was documented indirectly by the measurement of RVSP and microvascular morphometry (98).…”
Section: Methodsmentioning
confidence: 99%
“…At the completion of the chronic hypoxia protocol, mice underwent harvest for histology and hemodynamic measurement (Bryant et al, 2016 ). In indicated experiments, a separate group of mice underwent intraperitoneal injection with 0.018 U/g bleomycin (Thermo Fisher Scientific) or vehicle twice weekly for 28 days (Baran et al, 2007 ; Bryant et al, 2015 ). A group of vehicle- or bleomycin-treated mice were concomitantly dosed with 100 μL intraperitoneal liposomal clodronate (CL 2 MDP) 1 week prior to either bleomycin or chronic hypoxia exposure, and every 3 days thereafter, in order to induce lung macrophage apoptosis.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, the tissue response to low oxygen mediated by hypoxia-inducible factor (HIF)—a tightly conserved and regulated transcription factor across species—is known to be integral in the development of PH (Yu et al, 1999 ; Brusselmans et al, 2003 ). Building on these data, our group has recently uncovered a necessary role for tissue-specific—vascular endothelium derived—HIF in several models of PH (Bryant et al, 2015 , 2016 ). Specifically, we found that deletion of endothelial HIF leads to improved vascular barrier integrity in response to injury, and is associated with protection against pulmonary vessel “leakiness” leading to PH.…”
Section: Introductionmentioning
confidence: 99%